(untitled) (Bangladesh Journal of Anatomy, 2014)
Context: Teaching is a novel profession. Teaching is a science as well as an art. In case of medical teaching it is more important as it deals with human being oriented curriculum. Products of the medical teachers will deal with life and death. So medical teachers should have such qualities as role model in-front of students. It will help students to become future physicians with professionalism which the medical profession and people expect from them. Materials & Methods: A descriptive type of cross sectional study was conducted in different government and nongovernment medical colleges of Bangladesh to identify the qualities of medical teachers. The study population was the teachers of MBBS course who were working at least one year in medical colleges and were willing to co-operate and were available at the time of data collection. Sample size was 437. Self-administered structured questionnaire was used for the collection of data from the teachers. There were few open ended questions also. Results: Study revealed the generic fundamental qualities of a medical teacher are competent in respective subject, teach medical students daily, ethical person, nonthreatening attitude, assess the student in unbiased way, strength of personality, updated with relevant recent knowledge, not involve in grouping, preparing and presenting audio visual aids to make the teaching sessions attractive, strength of good communication (verbal, nonverbal, writing etc.), conduct research regularly, publish article in journals every year, act as role model, friendly with the colleagues, supportive for the staff, co-operate rationally with the administration, justified decision maker and good basic clinical care provider. Study also revealed the specific qualities of a medical teacher are sympathetic & empathetic dealings of a teacher towards patients, counsel to motivate students to be a self directed learner, motivate students for positive extracurricular activities (outdoor/indoor games, cultural functions, wall magazine, debate etc.), well behalf manager, fair personalities, wear decent well dress and not actively involved in politics. DOI: http://dx.doi.org/10.3329/bja.v11i2.20677 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 86-91